Нежность к ревущему зверю: роман / Александр Бахвалов - Бахвалов Александр Александрович (Современник, 1986)
Экземпляры: абонемент (20230726) / Инвентарный номер: 12048 / Авт.знак: Б 30 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6